2020
DOI: 10.1136/bmjopen-2019-035848
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, types and acceptability of pharmaceutical interventions about drug related problems in a general hospital: an open prospective cohort

Abstract: ObjectivesTo evaluate the incidence and types of drug-related problems (DRP) in a general teaching hospital and to evaluate the acceptability of pharmaceutical interventions by the medical team.DesignProspective cohort study during 2 years.SettingConducted in a Brazilian University Hospital.ParticipantsThe patient cohort consisted of 9303 patients with a total of 12 286 hospitalisation episodes.Primary outcome measuresDRP detected by pharmacists’ review of 100% medication orders using Pharmaceutical Care Netwo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 44 publications
0
13
1
Order By: Relevance
“…The most common DRPs were treatment ineffectiveness (11.5%) and treatment costs (5.90%), followed by the drug use process (18.4%) and the duration of treatment (31.0%). 21 A structured order review (French Society of Clinical Pharmacy instrument) was used to detect DRP in a study conducted in France by using a computerized physician order entry system (CPOE). In general, non-conformity to guidelines or contra-indications accounted for 29% of DRP, improper administration (19%), drug interactions (16%), and over dosage (12%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common DRPs were treatment ineffectiveness (11.5%) and treatment costs (5.90%), followed by the drug use process (18.4%) and the duration of treatment (31.0%). 21 A structured order review (French Society of Clinical Pharmacy instrument) was used to detect DRP in a study conducted in France by using a computerized physician order entry system (CPOE). In general, non-conformity to guidelines or contra-indications accounted for 29% of DRP, improper administration (19%), drug interactions (16%), and over dosage (12%).…”
Section: Discussionmentioning
confidence: 99%
“…A pharmacy service's first step toward preventing patient harm is to detect and classify potential DRP. 3,4 The identification and classification of potential DRPs by pharmacy services is crucial in reducing medication errors, adverse reactions, and length of stay, thus preventing patient harm. 5 There have been several strategies developed for detecting DRPs, including pharmacist review of medication orders (MO), computerized physician order entry (CPOE), and clinical decision support programs that allow the clinical pharmacist to actively participate within the healthcare team.…”
Section: Introductionmentioning
confidence: 99%
“…This result is not much different from the research reported by Herman and Sari in 2012 and Saldanha et al in 2020. In the "problem" domain, we found that the most frequent issue occurs the suboptimal therapeutic effect experienced by 20.7% of the total DRP [11] and has cumulative incidence at 9.21% [12].…”
Section: Discussionmentioning
confidence: 99%
“…As conducted by Abunahlah et al, it was found that the most common cause of DRP in patients was the presence of inappropriate drug combinations [13]. In contrast to Herman and Sari and Saldanha et al, they reported that the treatment duration is too long as the most cause issue of DRP in patients [11,12]. Thus, it can be concluded that drug selection is still the most common cause of inpatient care at the hospital, which agrees with studies reported.…”
Section: Discussionmentioning
confidence: 99%
“…Also, in a prospective cohort study (2020) conducted in a Brazilian University Hospital with a total of 12,286 hospitalisation episodes, the DRP detected using Pharmaceutical Care Network Europe 6.2 classification showed that drug use process (18.4%) and treatment duration (31.0%) were the main causes of DRP. 33 A very recent study (2021) conducted among elderly patients from surgical departments classified based on the Pharmaceutical Care Network Europe classification V8.02 reported drug selection (43.1%) and dose selection (43.1%) as the major causes of DRP from a total of 53,231 medication order forms. The results were in line with the current finding except for a higher percentage related to the number of reviewed sheets.…”
Section: Drug Related Problems In Clinical Pharmacist Sheets (Cps) Ov...mentioning
confidence: 99%